Exploration of Charge Transport Phenomena in Transition Metal Oxides for Energy Technologies - Burkhardt, Simon; Justus Liebig University Giessen (My University, 2019)
This Ph.D. project has been devoted to the exploration of charge transport phenomena in transition metal oxide (TMO) thin films and particles. For this purpose, new experimental methods combining microfabrication processes with different characterization methods from the fields of electrochemistry and/or optical spectroscopy were developed. These methods were employed to study the diffusion of hydrogen in tungsten trioxide (WO3) thin films, as well as electronic and ionic charge transport in single micrometer-sized lithiumnickel-cobalt-manganese-oxide (LiNi1/3Co1/3Mn1/3O2, NCM 111) secondary particles.By optically monitoring the diffusion of hydrogen in WO3 thin films, which resulted from the generation of a concentration gradient due to locally confined hydrogen insertion, the influence of the thin film morphology on the diffusion process was studied. The experimental data were modeled by simulations using a concentration-dependent diffusion process. Contrary to what is reported in the literature on WO3 thin films, the diffusion of hydrogen in polycrystalline thin films is faster than in amorphous thin films. Additionally, direct evidence for the influence of the hydrogen concentration on the diffusion processes was given, which differs depending on the thin film morphology. This novel finding potentially challenges the interpretation of experimental results from earlier studies on this material reported in literature. The results led to the first publication In Situ Monitoring of Lateral Hydrogen Diffusion in Amorphous and Polycrystalline WO3 Thin Films .The investigation of charge transport in single secondary NCM 111 particles was aimed at the characterization of ionic and electronic charge transport in single micrometer-sized particles of this material. As an electrochemically active material, which has the ability to reversibly store Li+ ions, it is used in cathodes in lithium-ion batteries (LIBs) and therefore belongs to the group of cathode active materials (CAMs). Although several reports on the investigation of electrochemical properties of single CAM particles can be found in the literature, ionic and electronic charge transport have not been studied on a single particle level before; thus the goal was to fill this experimental gap. This involved the development of a specially designed cell, the preparation of samples containing immobilized single particles on defined positions, the actual execution of different electrochemical experiments on single particles, the implementation of simulations, and modeling the observed correlations between derived parameters and the particle size. The results of these experiments and simulations suggested that the method introduced offers a successful approach for investigating charge transport on single-particle level and revealed an aspect of charge transport in such particles, which has not been previously reported: the identification of the preferred conduction pathways for lithium ions and electrons in this mixed-conducting material. The second publication Charge Transport in Single NCM Cathode Active Material Particles for Lithium-Ion Batteries Studied under Well-Defined Contact Conditions discusses the corresponding findings.In order to put the content of this thesis into a wider perspective, a short Introduction in an eponymous section is provided. The following section Fundamentals gives some basic information about the material systems investigated to facilitate the understanding of the results illustrated by the two peer-reviewed publications in the section Results and Discussion. The last section of this thesis Conclusions and Outlook summarizes the content and outlines future tasks and opportunities for further research, to which the presented experimental approaches provide access.
Keywords: ddc:530